Eksplorasi Hubungan Digital Marketing dan Customer Engagement terhadap Brand Awareness dengan Digital Literacy sebagai Variabel Moderasi pada Produk Lozy Hijab di Kabupaten Tasikmalaya - Fiana Putri; Ardhiansyah Ardhiansyah (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
This study aims to explore the influence of digital marketing and customer engagement on brand awareness, with digital literacy as a moderating variable for Lozy Hijab products in Tasikmalaya Regency. Despite the massive growth of the modest fashion industry, brands face challenges in translating social media reach into actual consumer interaction and awareness. This research employs a quantitative approach, collecting data from 100 female consumers through structured questionnaires. The data were analyzed using the SEM-PLS method via SmartPLS software. The results indicate that digital marketing, customer engagement, and digital literacy all have a positive and significant direct impact on brand awareness. Furthermore, digital literacy is proven to significantly strengthen the impact of both digital marketing and customer engagement on brand awareness. These findings categorize digital literacy as a quasi-moderator, indicating it functions as both a predictor and a moderator. This study concludes that high consumer digital proficiency is crucial for optimizing brand communication strategies. The practical implication suggests that brands should integrate digital education into their promotional content to foster more authentic brand recognition.